A general thermal stratification criterion for single and two-phase flows in a pipe after subcooled injection. (April 2018) - Gaillard, P.; Rodio, M.G.
Highlights: Analysis of thermal stratification in the liquid layer for single and two-phase flows. Criterion development for identifying thermal stratification in single and two-phase flows. Innovation points of the development: two-phase condition, condensation hypothesis and no-zero flow velocity in the pipe. The criterion results are in accordance with the experimental results for 124 on 129 test cases. Abstract: This paper aims to define a general criterion in order to predict the thermal stratification in a pipe induced by a subcooled injection. The mixing of two fluids with different temperatures yields a density difference, which could induce a thermal stratification between two liquids or two gases. Well-established criteria exist in literature for predicting the thermal stratification in single phase flows. However, experimental observations detected thermal stratification in two-phase flows as well, i.e. when a liquid-gas (or liquid-vapor) flow and a liquid flow at different temperature are mixed together. When a second phase exists, the mechanisms facilitating (or not) a thermal stratification are more complex to determine. In this paper, we propose a general criterion, able to identify the conditions for which a thermal stratification appears in both single and two-phase flows. We focus on the case of a liquid cold injection in a pipe, filled up with hot liquid or hot liquid/vapor flows. This criterion is then validated on a relevant experimental database that includes several fluid conditions.